Correlation of macronutrient intake and body fat precentage with menstrual cycle in famale students faculty of medicine Andalas University - Nadya Khaira Nurdi; Desmawati; Nita Afriani (Science Midwifery, 2023)
Indonesian Basic Health Research 2010 state that 13.7% of women in Indonesia with irregular menstrual cycles, 7,7% caused by lifestyle factors. West Sumatra is third highest province of irregular menstruation prevalence in Indonesia, which is 19.1%.The purpose of this research is to determine the relationship between macronutrient intake and body fat percentage with the menstrual cycle in female students Faculty of Medicine, Andalas University. This research type was an observational study with cross sectional research design. This research was conducted at the Faculty of Medicine, Andalas University in November 2021-September2022, with samples were 78 respondents. Sample techniques used systematic random sampling. Data were collected by physical examination and questionnaires. Bivariate analysis used independent sample t-test and multivariate analysis used logistic regression. The results of this research stated that the mean of macronutrient intake (calories, carbohydrates, fat, and protein) consumed by female students with irregular menstruation were 2839,87±229,32 kcal, 391,58±37,70 gram, 95,87±12,90 gram, 102,66±11,81 gram, and 42,71±4,42%. In addition, female students with normal menstruation were 2644,82±226,85 kcal, 369,31±40,40 gram, 86,69±14,32 gram, 96,85±10,95 gram, and 31,66±4,44%. This research showed that female students with irregular menstruation had higher of macronutrient intake and body fat percentage (p-value = <0.001, 0.016, 0.005, 0.028, and <0.001). The conclusion of this research is a significant relationship between macronutrient intake and body fat percentage with the menstrual cycle.